2014
DOI: 10.1371/journal.pone.0093016
|View full text |Cite
|
Sign up to set email alerts
|

A Single Whole-Body Low Dose X-Irradiation Does Not Affect L1, B1 and IAP Repeat Element DNA Methylation Longitudinally

Abstract: The low dose radioadaptive response has been shown to be protective against high doses of radiation as well as aging-induced genomic instability. We hypothesised that a single whole-body exposure of low dose radiation would induce a radioadaptive response thereby reducing or abrogating aging-related changes in repeat element DNA methylation in mice. Following sham or 10 mGy X-irradiation, serial peripheral blood sampling was performed and differences in Long Interspersed Nucleic Element 1 (L1), B1 and Intracis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…Irradiation of C57BL/6 mice with 10 mGy of x-rays (100–140 kVp at 13.9 mGy/min dose-rate) did not result in any persistent alterations in the DNA methylation of LINE-1, SINE B1 (non-autonomous retrotransposon that corresponds to human Alu elements), and Intracisternal A Particle (IAP) elements in peripheral blood, spleen, and liver tissues (Newman et al, 2014a). At the same time, exposure to a dose of 1 Gy of x-rays was characterized by the strain-, tissue-, sex-, and time-dependent alterations in methylation of the abovementioned repetitive elements (Newman et al, 2014b).…”
Section: Ionizing Radiation-induced Changes In the Dna Methylation Ofmentioning
confidence: 99%
“…Irradiation of C57BL/6 mice with 10 mGy of x-rays (100–140 kVp at 13.9 mGy/min dose-rate) did not result in any persistent alterations in the DNA methylation of LINE-1, SINE B1 (non-autonomous retrotransposon that corresponds to human Alu elements), and Intracisternal A Particle (IAP) elements in peripheral blood, spleen, and liver tissues (Newman et al, 2014a). At the same time, exposure to a dose of 1 Gy of x-rays was characterized by the strain-, tissue-, sex-, and time-dependent alterations in methylation of the abovementioned repetitive elements (Newman et al, 2014b).…”
Section: Ionizing Radiation-induced Changes In the Dna Methylation Ofmentioning
confidence: 99%
“…Exposure to 10 mGy of X-ray (using an attenuated 140 kVp X-ray beam (8 mm Al half value layer) from a Gulmay D3150 superficial X-ray unit; dose-rate of 13.9 mGy/min) did not result in any persistent alterations in the methylation of L1, SINE B1, and IAP TEs in peripheral blood, spleen, or liver of C57BL/6 mice [98]. Exposure to a higher dose of 1 Gy of X-irradiation led to strain-, tissue-, sex-, and time-dependent alterations in methylation of the TEs [99].…”
Section: Transposable Elements and Ionizing Radiationmentioning
confidence: 99%
“…For example, Newman et al, demonstrated that a single radiation dose in a mouse model comparable to human diagnostic radiation exposure did not result in significant long-or short-term changes to repeat elements or global DNA methylation patterns (88). Conversely, Kovalchuk et al, showed that chronic low-dose exposure proved to be a more potent inducer of epigenetic effects than the acute exposure.…”
Section: Effects Of Ldir On Epigenetic Gene Regulationmentioning
confidence: 99%